2011
DOI: 10.5251/abjna.2011.2.8.1160.1165
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics and carcass quality of broiler chicks under high stocking density fed vitamin E supplemented diet

Abstract: Two hundred and seventy, day-old Arbor Acre strain of broiler chicks were used for this research. The birds were randomly divided into five treatment groups of 10 birds/m 2 /replicate (0.1m 2 /bird) in Treatment 1 (positive control) while those in Treatments 2 (negative control), 3, 4 and 5 had 20 birds/m 2 /replicate (0.05m 2 /bird). Birds fed dietary Treatment 1 and 2 had no supplementation with vitamin E, whereas birds on dietary Treatments 3, 4 and 5 had 50mg/kg, 100mg/kg and 150 mg/kg vitamin E supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The findings were in agreement with Adebiyi et al (2011) and Mehala and Moorthy (2008) who reported better FCR values in birds fed with Vitamin E and Turmeric had no significant effect on the FCR in broilers. The results of the study revealed that birds fed with neem and its combinations had negative effect on FCR as compared to control and other treatment groups.…”
Section: Feed Conversion Ratiosupporting
confidence: 92%
“…The findings were in agreement with Adebiyi et al (2011) and Mehala and Moorthy (2008) who reported better FCR values in birds fed with Vitamin E and Turmeric had no significant effect on the FCR in broilers. The results of the study revealed that birds fed with neem and its combinations had negative effect on FCR as compared to control and other treatment groups.…”
Section: Feed Conversion Ratiosupporting
confidence: 92%
“…The birds that reared under closed house has received the significant effect with meatiness except the ratio breast muscle to the bone weight, the meatiness of the thigh and the breast. The researchers (Kurcubic et al, 2006); (Hossain et al, 2011) and (Adebiyi and Adu 2011) also agreed with the current research that the housing condition affected to the performances of the broilers.…”
Section: Effect Of the Housing Condition On The Meatiness Of The Broisupporting
confidence: 66%
“…When considering the previous studies (Adebiyi and Adu, 2011); (Traits et al, 2012) ( Hossain et al, 2011) and (Almasi et al, 2012) those were agreed that strain had significantly affected to the yield of the broiler production. It means the HC has more flesh, more edible part when comparing with inedible part, as well as the live weight and the bone weight.…”
Section: Effect Of the Housing Condition On The Meatiness Of The Broimentioning
confidence: 97%
“…In this respect, vitamin E supplementation has been investigated because of the reported benefits in laying hens during heat stress, and reduced body vitamin E levels during heat stress (Sahin et al, 2001). Many studies have reported that the inclusion of vitamin E in broiler diets not only reduces oxidative stress, but also improves the overall performance, as demonstrated by the higher body weight gain and reduced FCR of broilers fed vitamin E (Adebiyi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of vitamin E to Japanese quail diets significantly alleviated heat stress-related performance impairment, suggesting that dietary vitamin E supplementation is necessary under heat stress conditions (Sahin & Kucuk, 2001). The supplementation of vitamin E to broilers is also an important factor for the health of humans consuming chicken meat (Adebiyi et al, 2011) as it is known to improve meat quality by upregulating the expression of antioxidant enzyme genes in broilers (Niu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%